Cellular and circuit models of increased resting-state network gamma activity in schizophrenia. (3rd May 2016) - White, R.S.; Siegel, S.J.
Highlights: Gamma frequency activity contributes to cognitive function. Abnormalities in gamma activity are an endophenotype of schizophrenia. We address evidence that resting-state gamma power is elevated in schizophrenia. Modeling increased gamma in animals provides insights into the etiology of schizophrenia. Models of perturbed gamma activity may aid in the creation of potential therapeutics. Abstract: Schizophrenia (SCZ) is a disorder characterized by positive symptoms (hallucinations, delusions), negative symptoms (blunted affect, alogia, reduced sociability, and anhedonia), as well as persistent cognitive deficits (memory, concentration, and learning). While the biology underlying subjective experiences is difficult to study, abnormalities in electroencephalographic (EEG) measures offer a means to dissect potential circuit and cellular changes in brain function. EEG is indispensable for studying cerebral information processing due to the introduction of techniques for the decomposition of event-related activity into its frequency components. Specifically, brain activity in the gamma frequency range (30–80 Hz) is thought to underlie cognitive function and may be used as an endophenotype to aid in diagnosis and treatment of SCZ. In this review we address evidence indicating that there is increased resting-state gamma power in SCZ. We address how modeling this aspect of the illness in animals may help treatment development as well as providing insights into the etiology of SCZ.